Sensitivity Analysis and Correlation Experimental/Numerical FEM-BEM for Noise Reduction Assessment of an Engine Beauty Cover. (December 2015) - Siano, D.; Viscardi, M.; Aiello, R.
Abstract: In this paper a deep analysis on an internal combustion engine's beauty cover is carried out for identifying the best material for Noise Reduction improvements.The paper is organized as follows: Experimental modal analysis and comparison with the FEM simulation Experimental test on Noise Reduction assessment by using a novel experimental set up with a Pressure/Velocity Sound Intensity Numerical Boundary Element Analysis for computing the Noise Reduction on the engine cover Comparison between the experimental and BEM simulation The comparison of the experimental and FEM/BEM analysis results show a very good agreement in all investigated frequency range. The obtained results encourage to use the numerical model for further investigations aimed at the improvement of the acoustic performances. The implemented numerical procedure can be applied successfully not only in automotive field but also in all problems where material acoustic performances is due.